Scar evaluation in subperiosteal temporal pocket versus the one-layer flap technique in cochlear implantation using the Patient and Observer Scar Assessment Scale - BATMAN, ABDULLAH ÇAĞLAR (SPRINGER, 2019)
PurposeTo compare the local and intracranial complications, migration of the IRS, surgical duration, and quality of life with the subperiosteal pocket technique and the one-layer flap (OLF) technique using the Patient and Observer Scar Assessment Scale (POSAS).MethodsEight patients who underwent cochlear implantation. The patients were applied subscales of the POSAS and were asked to respond to the questionnaire items via a telephone conservation conducted by a physician. Another researcher evaluated the patients' photographs using OSAS. POSAS was applied to the patients to compare the differences of scar assessment in subperiosteal pocket technique and the OLF technique.ResultsThe surgical duration was 72.712.3min in the OLF group and 51.3 +/- 11.7min in the subperiosteal pocket group. The difference was statistically significant. No migration or intracranial complications were observed in either group. Patients in group 1 who underwent the subperiosteal technique were more satisfied than patients who received the OLF technique. However, there was no superiority between the two methods for the observer in scar assessment.Conclusion Although the surgical time is longer, the lack of difference in terms of scar formation from smaller incisions, and few intra- and post-operative complications in experienced hands ensure that the OLF technique is a safe and reliable method in cochlear implantation surgery.
Keywords: Cochlear implantation; Hearing loss; One-layer flap technique; Lazy-S incision; Patient and Observer Scar Assessment Scale; MINIMAL ACCESS; COMPLICATIONS; SURGERY